THE WESTERN EXPERIENCE IN FINANCIAL-ECONOMIC DEVELOPMENT MECHANISMS OF INNOVATION CLUSTERS - L. Kapranova (Управленческие науки)
It is mentioned in the article that the cluster approach to organizing and managing the manufacturing and innovative activity allows to solve the tasks of regional and branch development, to achieve the organizations’ competitive advantages, to attract investments, as well as to promote raising the interaction efficiency of states, business, research and educational establishments. The western experience of cluster approachinfinancial-economic developmentmechanisms is considered for better understanding of Russian economic development. Among them we highlight: direct financing, reduction in tax, legislative remedies of intellectual property, providing loans and target donations, as well as the creating the funds of implementing the innovations. Judging upon the international experience the usage of these mechanisms in regions’ development cluster model allows raising the effectiveness of regional clusters functioning. The implementation of cluster policy in western countries led to the growth of the labour productivity and innovative enterprises boom in clusters, to more intensive development of small and medium business, to growth of investments in stock capital, increasing the social and economic development of the territories, which in total strengthens considerably the state economy. The cluster initiatives in western countries allowed raising their competitiveness and optimizing the national economy management. It should be mentioned that one of the priority goals of cluster policy is the support of highly technological economy sectors (bio-technologies, IT etc.). Cluster initiatives assistance programs in western countries provide the declarative character of getting information about clusters for their further selection. The authorities organize the contest of collective applications. Besides the business sector is the major catalyst for innovations and financing the scientific researches and developments (R&D).Clusters are selected on competition principles where only the best get the assistance. Simultaneously several ministers are responsible for the implementation of cluster strategy. The programs financing may take place from different budgets: the own budgeting of the program, called-up capital from other federal and regional programs.